2010
DOI: 10.1182/blood-2009-09-244525
|View full text |Cite
|
Sign up to set email alerts
|

The detection of donor-directed, HLA-specific alloantibodies in recipients of unrelated hematopoietic cell transplantation is predictive of graft failure

Abstract: Donor-directed human leukocyte antigen (HLA)-specific allo-antibodies (DSAs) cause graft failure in animal models of hematopoietic stem cell transplantation (HCT). Archived pretransplantation sera from graft failure patients (n ‫؍‬ 37) and a matched case-control cohort (n ‫؍‬ 78) were tested to evaluate the role of DSAs in unrelated donor HCT. Controls were matched for disease, disease status, graft type, patient age, and transplantation year.Patients had acute myeloid leukemia, acute lymphoblastic leukemia, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
183
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(192 citation statements)
references
References 15 publications
6
183
2
1
Order By: Relevance
“…In the present study, haplo-SCT was defined as SCT from donors who share one of the two HLA haplotypes, regardless of the number of HLA-mismatched loci in A, B and DR locus in graftversus-host (GVH) or host-versus-graft (HVG) vectors; this definition was used because antibodies against HLA Ags, such as HLA-DP, which are not routinely tested in the settings of related donor transplantation, may also cause Ab-mediated rejection. 12,13 This study was approved by the Institutional Review Board of the Hyogo College of Medicine. All patients provided informed consent before participating in the study.…”
Section: Patientsmentioning
confidence: 99%
“…In the present study, haplo-SCT was defined as SCT from donors who share one of the two HLA haplotypes, regardless of the number of HLA-mismatched loci in A, B and DR locus in graftversus-host (GVH) or host-versus-graft (HVG) vectors; this definition was used because antibodies against HLA Ags, such as HLA-DP, which are not routinely tested in the settings of related donor transplantation, may also cause Ab-mediated rejection. 12,13 This study was approved by the Institutional Review Board of the Hyogo College of Medicine. All patients provided informed consent before participating in the study.…”
Section: Patientsmentioning
confidence: 99%
“…The incidence of graft failure is assumed to range from 2 to 20%, and the frequency depends on various factors such as stem cell source 1,2 and preconditioning regimen, [3][4][5] underlying disease, 5 HLA disparity 2,6,7 and the presence of anti-HLA Abs. 8 Salvage HSCT can rescue pGF patients, [9][10][11][12][13][14] and recent studies on adult pGF patients have showed the feasibility of using reduced-intensity conditioning containing fludarabine (FLU) and low-dose irradiation, 13,[15][16][17] including short-term preconditioning regimen 10,18 and an advantage of PBSC as the stem cell source for salvage HSCT. 19,20 However, the management of pGF patients is usually difficult because of their poor clinical status.…”
Section: Introductionmentioning
confidence: 99%
“…18 Recipient antibodies against mismatched donor HLA-DP have also been shown in 10/10 matched MUD alloSCT to be associated with a higher incidence of graft failure and mortality. 19 Risk of rejection also increases with increasing numbers of mismatches at HLA-A, -B, -C and -DR loci. 20 Patients receiving dUCBT often have a period of transient mixed chimerism and almost universally have eventual dominance of one cord and disappearance of the other.…”
mentioning
confidence: 99%